A Comparative Assessment of Spatial Factors Influencing Women’s Access to High-Skilled Employment in Albania, Bulgaria, and Türkiye - Mayen Huerta, Carolina; Ivanescu, Clara; Gontariu, Dragos (European Journal of Geography, 2026)
Women’s labor force participation remains limited in many parts of Southeast Europe and surrounding regions, including Albania, Bulgaria, and Türkiye. While prior research has examined social and institutional drivers of low female labor force participation, the influence of geographic factors on women’s access to employment has received comparatively less attention. This study addresses that gap by applying the Geospatial Women’s Employment Analytical Framework (GeoWEAF) to assess how place-based factors shape women’s high-skilled employment opportunities in Albania, Bulgaria, and Türkiye. These countries were selected due to their shared challenges in advancing gender equality in employment, as well as their differing institutional contexts, development trajectories, and stages of European Union integration, making them a valuable basis for comparative analysis. This application modifies the original framework by excluding the environmental hazards factor, given its ambiguous and non-directional effects, and by introducing spatially disaggregated representations of attitudes toward women in STEM and digital inclusion, which were originally applied at the national level. It also revises the methodology for assessing active transport to address data limitations and adjusts both the scoring and weighting schemes to better capture the contextual and spatial variation in the selected countries. The analysis reveals that, although urban areas generally exhibit higher levels of enablement, substantial intra-urban variation persists, with some areas within cities displaying levels of enablement comparable to rural regions. These findings highlight the importance of incorporating spatial analysis into gender and labor market research. Mapping underserved areas in services and infrastructure, and those exhibiting heightened vulnerability to risks, can enhance the targeting of interventions to accelerate women’s inclusion in the workforce. Highlights: This study used GeoWEAF to examine spatial inequalities in women’s access to high-skilled employment. The results reveal persistent spatial disparities, including within major urban areas. Spatial analysis should play a central role in gender-focused labor diagnostics to inform inclusive development policies.